98.7k views
4 votes
ASAP need help confused

ASAP need help confused-example-1
User Reoxey
by
5.1k points

2 Answers

7 votes

Answer:

b =
(3z + 6)/(3z+1)

Explanation:

Simply solve for "b" , so the formula will be

b = .....

z =
(-b+6)/(3b-3) ( b > 0 )

z(3b - 3) = - b + 6

3zb - 3z = - b + 6

3zb + b = 3z + 6

b( 3z + 1 ) = 3z + 6

b =
(3z + 6)/(3z+1)

User Edwin De Koning
by
5.3k points
2 votes

Answer:

b= (3z-6)/(1+3z)

Explanation:

z=(-b+6)/(3b-3)

cross multiple

z(3b-3)=-b+6

open the bracket

3bz-3z=-b+6

make -b the subject of the formula

-b = 3bz-3z-6

-b - 3bz = -3z - 6

factorize the left hand side...

-b(1+3z) = -3z-6

make -b the subject of the formula again

-b = -(3z-6)/(1+3z)

cancel the minus at both sides...

b = (3z-6)/(1+3z)

User Stephen Jacob
by
5.8k points